Feasibility of agricultural biomass in Southeast Asia for enzymes production - Jenol, M. A.; Chu, P. H.; Ramle, I. K.; Joyce, L. J. W.; Lai-Yee, P.; Ibrahim, M. F.; Alitheen, N. B.; Osman, M. A.; Abd Gani, S.; Abd-Aziz, S. (Elsevier, 2024)
The agricultural sector in Southeast Asia holds significant importance for the region’s economies, playing a vital role in employment and ensuring food security. Major contributors to this sector include Indonesia, Vietnam, Thailand, the Philippines, and Malaysia. In fact, the agricultural sector has contributed to 10–30 % of gross domestic product in most Southeast Asia countries. However, the high demand for agricultural products has led to the generation of excessive biomass, which accounted for approximately 100–200 millions metric tonnes annually, much of which remains unused. In response, there has been a growing trend towards biomass biorefinery, producing value-added products such as bioenergy, biofuels, and bioproducts. Several key challenges in utilizing biomass as a feedstock are the high cost of enzymes required for conversion processes, as well as pretreatment required in the agricultural biomass utilization, which hinders commercialization efforts. To address this challenge, leveraging microorganisms for enzyme production using biomass itself has emerged as a promising solution. This review aims to provide the comprehensive potential utilization of major agricultural biomass in Southeast Asia in bioconversion of valuable product, in such enzyme. This work intends to enlighten the potential and feasibilities factors driving the transition from traditional agricultural practices to modern enzymatic production. It delves into fermentation factors and condition, emphasizing the need for sustainable and efficient enzymatic conversion processes to fully exploit the potential of agricultural biomass for industrial applications.